2021
DOI: 10.3390/jcm10020210
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Choroid and Its Relationship with the Outer Retina in Patients with Diabetes Mellitus Using Binarization Techniques Based on Spectral-Domain Optical Coherence Tomography

Abstract: (1) Background: We aimed to reveal the relationship between the choroid and the outer retina with optical coherence tomography (OCT) in patients with diabetes mellitus (DM) with mild or no diabetic retinopathy (DR) in order to find early biomarkers for progressing retinopathy. (2) Methods: We performed a prospective study including 61 eyes of patients with type 1 or type 2 DM and 36 eyes of healthy controls. All subjects were imaged with Spectralis OCT. The choroid was assesseed using enhanced depth imaging OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…Our findings are partly in agreement with the results published by Wang et al, according to whom DR patients presented with significantly lower choroidal, ORL, and RPE thickness than the controls, without significant differences observed between patients with concomitant DME and without [17]. Damian et al found thinner ONL and ORL in patients in whom diabetes coexisted with mild DR or lack thereof, without concomitant DME [54]. Other authors reported outer retinal atrophic changes in DME [13] with PROS (photoreceptor outer segment) shortening [13,44].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are partly in agreement with the results published by Wang et al, according to whom DR patients presented with significantly lower choroidal, ORL, and RPE thickness than the controls, without significant differences observed between patients with concomitant DME and without [17]. Damian et al found thinner ONL and ORL in patients in whom diabetes coexisted with mild DR or lack thereof, without concomitant DME [54]. Other authors reported outer retinal atrophic changes in DME [13] with PROS (photoreceptor outer segment) shortening [13,44].…”
Section: Discussionsupporting
confidence: 93%
“…Consistently with previous reports [54,55], we found no significant correlations between choroidal parameters (CVI and choroidal thickness) and outer retinal parameters in healthy controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Damian and al. found decreased RPE thickness in almost all quadrants in the PDR-DMO group as opposed to NPDR-DMO group, where the quadrants number was lower [86]. This finding was explained by a disruption of the RPEphotoreceptors complex due to ischemia and level of inflammation that varies according to the stage of DR. Cysts larger than >200 μm in the outer nuclear layer (ONL) are seen in advanced stages of DME and may cause irreversible damage to visual functions.…”
Section: Intraretinal Cystoid Spacesmentioning
confidence: 85%
“…Tan et al found no differences in TCA, LA, and SA in patients without DM versus patients with DM with or without DR [ 23 ]. Conversely, Damian et al reported a significant difference between normal subjects and pooled DM and DM with mild NPDR subjects regarding TCA, LA, and SA, but no differences when they evaluated the DM versus DM with mild NPDR subjects [ 54 ].…”
Section: Discussionmentioning
confidence: 99%